Effects of Salvia miltiorrhiza and Radix astragali on the TGF-Î²/Smad/Wnt pathway and the pathological process of liver fibrosis in rats - Cao, Tingting; Lu, Yuan; Zhu, Minwei; Cheng, Jiafei; Ye, Bai; Fang, Nanyuan; Cui, Yueping; Xue, Boyu; Lari Najafi, Moslem; Kazemi, Elham (Cellular and Molecular Biology, 2020)
Traditional Chinese medicine has made some progress in the study of liver fibrosis, and provides valuable experience for clinical treatment of liver fibrosis. The aim of this study was to investigate the rationality of compatibility use of Salvia miltiorrhiza and Radix astragali on liver fibrosis in rats. For this purpose, the rat model of liver fibrosis was treated with single or different compatibilities of herbals extracts for 4 weeks. Saline and colchicine were set as a negative and positive control, respectively. Liver histopathology, liver function, and expressions of key proteins in the TGF-Î²/Smad/Wnt pathway were assessed. Results showed that compared with colchicine, herbal extracts showed better ability to reduce deposition of Î±-SMA and type I collagen, and improve liver function. The effect of R. astragali extracts and 1:1 compound on improving liver fibrosis and liver function was relatively better than other treatment options. The compound groups showed a particularly significant effect on reducing Cyclin D1 expression. It was concluded that the 1:1 compatibility use of S. miltiorrhiza extracts and R. astragali extracts can preferably attenuate liver fibrosis by regulating the expression of TGF-Î²1 and Cyclin D1.